Evaluation of idiopathic transverse myelitis revealing specific myelopathy diagnoses. (9th January 2018) - Zalewski, Nicholas L.; Flanagan, Eoin P.; Keegan, B. Mark
Abstract : Objective: To evaluate specific myelopathy diagnoses made in patients with suspected idiopathic transverse myelitis (ITM). Methods: A total of 226 patients 18 years and older were referred to Mayo Clinic Neurology for suspected ITM from December 1, 2010, to December 31, 2015. Electronic medical records were reviewed for detailed clinical presentation and course, laboratory and electrophysiologic investigations, and neuroimaging to determine the etiology. Current diagnostic criteria for ITM and alternative myelopathy diagnoses were applied. All cases where any discrepancy was suspected from the final reported clinical diagnosis were reviewed by each author and a consensus final diagnosis was made. Results: The diagnostic criteria for ITM were met in 41 of 226 patients (18.1%). In 158 patients (69.9%), an alternative specific myelopathy diagnosis was made: multiple sclerosis or clinically isolated syndrome, 75; vascular myelopathy, 41; neurosarcoidosis, 12; neuromyelitis optica spectrum disorder, 12; myelin oligodendrocyte glycoprotein myelopathy, 5; neoplastic, 4; compressive, 3; nutritional, 3; infectious, 2; and other, 2. A myelopathy was not confirmed in 27 patients. Time from symptom onset to final clinical diagnosis in patients without ITM was a median of 9 months (range 0–288). Fifty-five patients (24%) required treatment changes according to their final clinical diagnosis. Conclusions: The majority of patients with suspected ITM have an alternative specific myelopathy diagnosis. A presumptive diagnosis of ITM can lead to premature diagnostic conclusions affecting patient treatment.